2010
DOI: 10.1175/2010waf2222375.1
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Dvorak Technique–Based Tropical Cyclone Intensity Estimates

Abstract: The satellite-based Dvorak technique (DVKT) is the most widely available and readily used tool for operationally estimating the maximum wind speeds associated with tropical cyclones. The DVKT itself produces internally consistent results, is reproducible, and has shown practical accuracy given the high cost of in situ or airborne observations. For these reasons, the DVKT has been used in a reasonably uniform manner globally for approximately 20 years. Despite the nearly universal use of this technique, relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 23 publications
1
77
0
Order By: Relevance
“…Such a project could improve the CC consensus by including corrections for biases in TC intensity estimates that originate from the Dvorak technique, as demonstrated in Knaff et al (2010). The information presented here is just a hint of what is possible with the data that have been (and are still continuously being) collected.…”
Section: Su M M a Ry A N D Fu T U Re W O Rkmentioning
confidence: 89%
See 1 more Smart Citation
“…Such a project could improve the CC consensus by including corrections for biases in TC intensity estimates that originate from the Dvorak technique, as demonstrated in Knaff et al (2010). The information presented here is just a hint of what is possible with the data that have been (and are still continuously being) collected.…”
Section: Su M M a Ry A N D Fu T U Re W O Rkmentioning
confidence: 89%
“…In general, the technique involves the interpretation of an IR image of a TC and the application of a number of constraints and set procedures. Dvorak has been used consistently at all global TC forecast agencies for at least the last 20 years, and validation studies (e.g., Gaby et al 1980;Knaff et al 2010) have shown that average differences between Dvorak intensity estimates and aircraft reconnaissance-based best-track data are quite low, ranging from 1.5 to 9 knots (kt; 1 kt = 0.51 m s -1 ).…”
Section: T H E Crow D So U Rcin G O F Scien Cementioning
confidence: 99%
“…Even at the most basic level, the definition of wind speed varies considerably around the globe, with 1, 10, 3 and even 2-min averaging periods in use (Harper et al 2008). Some homogenization is provided by the universal use of the Dvorak satellite interpretation technique (Velden et al 2006;Knaff et al 2010) but there remain issues with the approaches used to convert from the satellite pattern code to a surface wind speed.…”
Section: Datamentioning
confidence: 99%
“…There may have been a consistent change in analysis practice and/or satellite data that led to increasing analysis of intense systems over the time period (Knaff et al 2010). We check this potential impact by using the objective satellite-based reanalysis undertaken by Kossin et al (2007).…”
Section: Analysis Issuesmentioning
confidence: 99%
“…Most contemporary satellite-based intensity estimates are based on the Dvorak technique (Velden et al 2006), in which intensity is estimated from image patterns and infraredderived cloud-top temperatures. Satellite-based storm intensities are usually within roughly 10 kt of aircraft reconnaissance-based estimates, at least since 1989 (Knaff et al 2010). Some discussion of the effect of Dvorak-type techniques on tropical cyclone intensity estimation can be found in Schreck et al (2014).…”
Section: A Observationsmentioning
confidence: 99%